Functional characterization of Fur in iron metabolism, oxidative stress resistance and virulence of Riemerella anatipestifer - Mi Huang; Mafeng Liu; Jiajun Liu; Dekang Zhu; Qianying Tang; Renyong Jia; Shun Chen; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; Juan Huang; et al. (Veterinary Research, 2021)
Abstract Iron is essential for most bacteria to survive, but excessive iron leads to damage by the Fenton reaction. Therefore, the concentration of intracellular free iron must be strictly controlled in bacteria. Riemerella anatipestifer (R. anatipestifer), a Gram-negative bacterium, encodes the iron uptake system. However, the iron homeostasis mechanism remains largely unknown. In this study, it was shown that compared with the wild type R. anatipestifer CH-1, R. anatipestifer CH-1Δfur was more sensitive to streptonigrin, and this effect was alleviated when the bacteria were cultured in iron-depleted medium, suggesting that the fur mutant led to excess iron accumulation inside cells. Similarly, compared with R. anatipestifer CH-1∆recA, R. anatipestifer CH-1∆recAΔfur was more sensitive to H2O2-induced oxidative stress when the bacteria were grown in iron-rich medium rather than iron-depleted medium. Accordingly, it was shown that R. anatipestifer CH-1∆recAΔfur produced more intracellular ROS than R. anatipestifer CH-1∆recA in iron-rich medium. Electrophoretic mobility shift assays showed that R. anatipestifer CH-1 Fur suppressed the transcription of putative iron uptake genes through binding to their promoter regions. Finally, it was shown that compared with the wild type, R. anatipestifer CH-1Δfur was significantly attenuated in ducklings and that the colonization ability of R. anatipestifer CH-1Δfur in various tissues or organs was decreased. All these results suggested that Fur is important for iron homeostasis in R. anatipestifer and its pathogenic mechanism.